Analisis Efektivitas Dan Kontribusi Pengelolaan Penerimaan Negara Bukan Pajak (PNBP) pada Sekretariat Jenderal Kementerian Pertanian - Fatimah Ahmad; Tresno Ekajaya; Surya Anugrah (Jurnal Akuntansi, Perpajakan dan Auditing, 2026)
Non-Tax State Revenue (PNBP) must be managed effectively as a major source of state revenue outside taxation. This study analyzes PNBP effectiveness, the contribution of each PNBP source, supporting and inhibiting factors, and optimization strategies at the Secretariat General of the Ministry of Agriculture for 2023-2025. A mixed-method sequential explanatory design combined quantitative ratio analysis with qualitative thematic analysis using NVivo, based on interviews with three informants. Results show PNBP effectiveness consistently falls into the Very Effective category, averaging 132.26%, highest in 2025 (151.02%) and lowest in 2023 (126.17%). Administration and Law Enforcement Revenue is the most dominant source (68.72%, Very Good), followed by Revenue from Sales and State Asset Management, categorized as Moderate (25.61%), while four remaining sources are Very Poor. Supporting factors include asset commitment and digitalization; inhibiting factors include limited human resources and bureaucratic approval. The study recommends digitalization, diversification, cooperation modernization, and stronger oversight.